Acercamiento a la enfermedad renal crónica en caninos y felinos geriátricos (2023)
This paper seeks to compile updated aspects related to Chronic Kidney Disease (CKD) both in geriatric canines and cats. Worldwide this disease affects 0.5–1.5% of canines and 1–3% of cats, with mortality rates of 5% and 3%, respectively.The literature rev